Legal Impact From Lambe Turah Account Relating To Article Of Insult And Prohibited Conduct - Anjani, Risa Gia; Ramadhani, Dwi Aryanti; Dirkareshza, Rianda (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
Instagram is an information dissemination platform that is very attractive to Indonesians. The popularity of the Lambe Turah gossip account on social media Instagram is not necessarily free from the applicable legal rules, that all social media activities related to insulting and spreading the privacy of others is a violation that refers to the Criminal Code and the Law Information and Electronic Transactions. The research method in this scientific work is a normative-juridical study, using the statute approach and analyzed qualitatively. Lambe Turah's